Severe cutaneous reactions to drugs in the setting of a general hospital - Luciana Rosa Grando; Tatiana Aline Berger Schmitt; Renato Marchiori Bakos (Anais Brasileiros de Dermatologia, 2014)
BACKGROUND: Cutaneous drug reactions are frequently found. Assessing the clinical and epidemiological profile of severe forms is extremely relevant for their better recognition and management. Few studies have assessed the severe forms of cutaneous drug reactions in patients hospitalized in our setting. OBJECTIVES: To assess the clinical and epidemiological aspects of severe cutaneous adverse reactions to drugs in a tertiary hospital in Porto Alegre, Brazil. METHODS: All cases of severe cutaneous adverse reactions to drugs in patients hospitalized from January/2005 to December/2010 were retrospectively analyzed for clinical and epidemiological variables. Cases of Stevens-Johnson Syndrome, Toxic Epidermal Necrolysis, drug hypersensitivity syndrome or Drug Reaction with Eosinophilia and Systemic Symptoms and acute generalized exanthematous pustulosis were included. RESULTS: An occurrence rate of 1 serious reaction for every 3,048 inpatients was found (total of 173,767 inpatients admitted in the period). Drug Reaction with Eosinophilia and Systemic Symptoms was the most frequent presentation. The drugs most frequently involved were anticonvulsants (40.4%), antibiotics (26.3%), and analgesics/anti-inflammatory drugs (10.5%). Thirty seven patients (64.9%) were admitted to hospital because of the cutaneous drug reaction. Ten patients (17.5%) died and in most of those (60%), the drug causing the reaction could not be determined. CONCLUSIONS: The frequency of severe cutaneous adverse reactions to drugs in our setting is significant. Drug Reaction with Eosinophilia and Systemic Symptoms seems to be the most frequent presentation of severe cutaneous drug reactions. Most patients developed cutaneous drug reactions outside the hospital. Mortality rates were higher for Toxic Epidermal Necrolysis and this presentation significantly affected older people. Not knowing the drug causing the reaction was related to mortality.